An Investigation of Differential Item Functioning and Differential Test Functioning Of Swusat during 2010-2013 - Sirikit, Ruangdech; Choptham, Manida; Mahalawalert, Panwasn; Tagontong, Navarin; Apinyapibal, Supa (Scholar: Human Sciences, 2017)
The purpose of this research was to analyze the differential item functioning (DIF) and the differential test functioning (DTF) of scholastic aptitude test (SWUSAT) for groups of students and classified by gender. The data used in this research is the secondary data from Srinakharinwirot University Scholastic Aptitude Test (SWUSAT) year 2011 and 2013. SWUSAT test consists of 4 subjects and 10 tests. There are verbal ability test, number ability test, reasoning ability test and spatial ability test. The data analysis was analyzed in 2 steps. The first step was analyzing descriptive statistics. In the second step were analyzed differential item functioning (DIF) and differential test functioning (DTF) by using the DIFAS program. The results of DIF and DTF analysis for all 10 tests in year 2011. Gender was the characteristic that found DIF all 10 tests. The percentage of item number that found DIF between 10% - 46.67%. There are 4 tests that most of items favors female group. There are 3 tests that most of items favors male group and there are 3 tests that the number of items favors female group equal favors male group. For Differential test functioning (DTF), there are 8 tests that have small level. The results of DIF and DTF analysis for all 10 tests in year 2013. Gender was the characteristic that found DIF all 10 tests. The percentage of item number that found DIF between 6.67% - 60%. There are 5 tests that most of items favors female group and 2 tests that most of items favors male group. There are 3 tests that the number of items favors female group equal favors male group. For Differential test functioning (DTF), there are 8 tests that have small level.